2010
DOI: 10.1111/j.2042-3306.2010.00123.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum biomarker levels for musculoskeletal disease in two‐ and three‐year‐old racing Thoroughbred horses: A prospective study of 130 horses

Abstract: Biomarkers have the potential to be used as a screening aid prior to musculoskeletal injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 35 publications
(35 reference statements)
3
54
1
Order By: Relevance
“…MMP‐3 was selected as it degrades other minor proteins in tendon matrix, including collagens III, IV, IX, and X, and also proteoglycans and elastin 28, 29, 30, 31, 32, 33. The C1,2C (or COL 2 3/4C short) antibody detects the carboxy terminus of fragmented type I and II collagen, cleaved by collagenases MMP‐1, MMP‐8 or MMP‐13 21, 34, 35, 36, 37…”
Section: Methodsmentioning
confidence: 99%
“…MMP‐3 was selected as it degrades other minor proteins in tendon matrix, including collagens III, IV, IX, and X, and also proteoglycans and elastin 28, 29, 30, 31, 32, 33. The C1,2C (or COL 2 3/4C short) antibody detects the carboxy terminus of fragmented type I and II collagen, cleaved by collagenases MMP‐1, MMP‐8 or MMP‐13 21, 34, 35, 36, 37…”
Section: Methodsmentioning
confidence: 99%
“…Current research into the identification of serum biomarkers suggests that these may become valuable indicators of pathology in the future and allow for detection of subclinical disease. [57][58][59] In RER, suggestive clinical signs are associated with significantly elevated serum creatinine kinase (CK) enzyme activity 4 to 6 hours postexercise, indicating cell membrane damage because of myonecrosis. 56 Serum muscle enzyme activity does not always reflect the severity of clinical signs, but serial measurements can be used to determine the progression of injury.…”
Section: Diagnosismentioning
confidence: 99%
“…In the case of naturally occurring equine traumatic OA, the Fourier transform infrared spectroscopy (FTIR) approach has been confirmed as highly accurate for synovial fluid when compared to arthroscopy . The limitations of such studies are that they have been conducted on clinically apparent cases and have not been tested in a preclinical population of horses for which prospective synovial fluid analysis would be impractical …”
Section: Equine Musculoskeletal Biomarkers: Current Knowledge and Futmentioning
confidence: 99%
“…12 A clinical study in 238 racehorses, employing monthly musculoskeletal examinations and blood samples, showed that it was possible to correctly predict horses that would sustain an injury 74% of the time. 34 Recent work evaluating proteinases has shown that: (i) the presence of lumican and a 29 kD lumican catabolite increased with the onset and progression of OA 35,36 ; (ii) a splice variant of one of the aggrecanases (ADAMTS4) was identified that appears to be specifically synthesized by human OA synovium and is associated with aggrecan degradation in the superficial zone of articular cartilage 37 ; and (iii) synovial fluid ADAMTS4 activity is a marker of inflammation and effusion. 38 Such findings have biologic/disease rationale as confirmed by OA onset in a STR/ORT mouse model being significantly reduced using monoclonal antibodies directed against substrate recognition domains of ADAMTS5.…”
Section: Transcriptome Analyses Of Meniscus and Anterior Cruciate Ligmentioning
confidence: 99%